2017
DOI: 10.3390/ijms18081686
|View full text |Cite
|
Sign up to set email alerts
|

Intramitochondrial Ascorbic Acid Enhances the Formation of Mitochondrial Superoxide Induced by Peroxynitrite via a Ca2+-Independent Mechanism

Abstract: Exposure of U937 cells to peroxynitrite promotes mitochondrial superoxide formation via a mechanism dependent on both inhibition of complex III and increased mitochondrial Ca2+ accumulation. Otherwise inactive concentrations of the oxidant produced the same maximal effects in the presence of either complex III inhibitors or agents mobilizing Ca2+ from the ryanodine receptor and enforcing its mitochondrial accumulation. l-Ascorbic acid (AA) produced similar enhancing effects in terms of superoxide formation, DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Both mechanisms are based on the assumption of overproduction of hydrogen peroxide due to one-electron menadione/ascorbate redox cycling [ 23 25 , 28 , 30 , 57 , 79 ]. All these events are reported at high concentrations of M/A (>5/500 μ M/ μ M), and conclusions are based on indirect evidence such as (i) effects of catalase, metal chelators, antioxidants, and end-products of oxidative stress in M/A-treated cells [ 23 25 , 28 , 57 , 65 ] or (iii) production of superoxide and/or hydrogen peroxide in cells treated with menadione or ascorbate alone [ 79 84 ]. Based on our knowledge, there are no data about direct detection of production and/or degradation of superoxide and/or hydrogen peroxide in M/A-treated cells.…”
Section: Resultsmentioning
confidence: 99%
“…Both mechanisms are based on the assumption of overproduction of hydrogen peroxide due to one-electron menadione/ascorbate redox cycling [ 23 25 , 28 , 30 , 57 , 79 ]. All these events are reported at high concentrations of M/A (>5/500 μ M/ μ M), and conclusions are based on indirect evidence such as (i) effects of catalase, metal chelators, antioxidants, and end-products of oxidative stress in M/A-treated cells [ 23 25 , 28 , 57 , 65 ] or (iii) production of superoxide and/or hydrogen peroxide in cells treated with menadione or ascorbate alone [ 79 84 ]. Based on our knowledge, there are no data about direct detection of production and/or degradation of superoxide and/or hydrogen peroxide in M/A-treated cells.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, Vitamin C is highly concentrated within mitochondria [711]. For example, when U937 cells (a human leukaemia cell line) were incubated for only 15 minutes in media containing 3 μM Vitamin C, it was very efficiently transported to the mitochondria, reaching a level of 5 mM – being concentrated ~1,700-fold [8]. Mitochondrial transport of Vitamin C is accomplished by the sodium-coupled Vitamin C transporter 2 (SVCT2) [710], also known as SLC23A2, although other novel mitochondrial transporters have been suggested [11].…”
Section: Discussionmentioning
confidence: 99%
“…As an example, we found that preexposure of U937 cells to AA enhances their susceptibility to the deleterious effects mediated by various hydroperoxides, in particular peroxynitrite [ 11 , 46 ]. We also found that the mitochondrial fraction of AA is specifically linked to the enhanced cyto-genotoxicity induced by peroxynitrite [ 30 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…We also employed a different strategy based on our previous findings indicating that preexposure of undifferentiated U937 cells to AA enhances their susceptibility to the deleterious effects mediated by peroxynitrite [ 11 , 46 ]. These enhancing effects are based on the notion that mitochondrial AA increases the mitochondrial formation of superoxide mediated by peroxynitrite, via a Ca 2+ -independent mechanism associated with inhibition of complex III [ 30 , 46 ]. As expected, preexposure to 10 μ M AA significantly increased mitochondrial superoxide formation and its downstream deleterious effects, induced by peroxynitrite in the undifferentiated cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation